The theme of state ethics in Aristophanes’ The Birds - Carvalho, Tiago Nascimento (Revista Archai, 2025)
This paper evaluates the possibility of under-standing the Ethics of the State as a proposed reading of the famous comedy of Aristophanes’ The Birds. For this it is essential that it be demonstrated to be called the myth of the ideal city, a literary allegory of the ideal city in versus the foundations of the current models the Greek city-states, but Athens itself, on speculation that the political errors and vices social environ-ment of the polis is this analogy that comes to the discussion of the ethical standards required minimum in any set of social organization